Grammatical Errors in the English Version of Indonesia’s Official Tourism Website - Maria Erlita Cipta Sari (Universitas Gadjah Mada, 2013)
This research attempts to investigate the grammatical errors occuring in the official website of Indonesia’s tourism managed by the Tourism and Creative Economy Ministry of the Republic of Indonesia. It classifies the grammatical errors based on their lingustic categories. The data used in this research were taken from the articles containing grammatical errors. The results show that from 11037 words, 150 errors (13.59 per 1000 words) were found. The errors were evenly distributed across the three menus under investigation, with those in the News menu (15.46 errors per 1000 words) being slightly greater than those in the Discover Indonesia menu (12.97) and the Events menu (12.65). Furthermore, of the 150 errors, 131 (87.33%) belong to the syntactic category and only 19 (12.67%) belong to the morphological category. Out of the 19 morphological errors, the most frequent errors occured in the incorrect use of nominal modifiers (9 or 47.37%), followed by the incorrect use of third person singular verb (5 or 26.32%). As for the syntactic errors, the most common (102 or 77.87%) occured in the use of the noun phrase, followed by the incorrect use of the verb phrase (15 or 11.45%). Out of the 102 errors in the use of the noun phrase, most errors (65 or 63.72%) happened because of the omission of the articles, especially the definite article. The results seem to reflect the ability of the writers which do not clearly understand about the occasions when the definite article must be used.